A referral pathway for potentially abnormal neurodevelopment in children with heart disease in the United Kingdom: a Delphi consensus. Issue 1 (21st April 2020) - Hoskote, Aparna; Wray, Jo; Banks, Victoria; Brown, Katherine; Lakhanpaul, Monica
Abstract : Introduction: Children with congenital heart disease have complex medical and neurodevelopmental needs. We aimed to develop a multi-professional consensus-based referral pathway applicable to action the results of the brief developmental assessment (BDA), a validated early recognition tool, that categorises the neurodevelopmental status as green (appropriate for age), amber (equivocal) or red (delayed) in children aged between 4 months and 5 years. Methods: A Delphi consensus survey detailing two scenarios—a child categorised as delayed (red) and another as equivocal (amber) on administration of the BDA at the time of discharge from the tertiary centre—was sent to 80 expert professionals from primary, secondary and tertiary care seeking agreement on next steps and referral pathways. An iterative process was proposed with a pre-defined rule of 75% for consensus. Results: The survey was completed by 77 Delphi panel experts in Round 1, 73 in Round 2 and 70 in Round 3. Consensus was achieved (1) for the child with amber or red BDA, the child should be under the care of a paediatrician with expertise in cardiology (PEC) (or general paediatrician if no PEC) based at their local hospital, (2) for the child with red BDA, the PEC should initiate referral to community services at first assessment, (3) for child with amber BDA, a re-assessment by the health visitor should occur within 1–2 months, with referral to community services and notification to the PEC if on-going concerns. Conclusions: The Delphi process enabled a consensus to be reached between health professionals on referral pathways for specialist neurodevelopmental assessment/treatment for children with heart disease, in response to amber or red BDA results. The agreed referral pathway, if implemented, could underpin a national guideline to address and intervene on the neurodevelopmental difficulties in children with heart disease.